Evaluasi Artificial Lift Esp Menggunakan Metodanalisinodal Untuk Meningkatkan Laju Sumur X Pada Lapangan Y - Ceroline Bakarbessy; Agus Wahyudi; Alexander A. Patty (Department of Mechanical Engineering, 2023)
Petroleum is an important component in the communityâ€™s everyday life. It is needed both by the community and the industry, therefore the oil production activity are carried out in the field. Oil production in the field has always been closely tied to the decrease in reservoir pressure, causing several issues such as production rate reduction, pump setting depth decrease and reservoir decrease, therefore an artificial lift must be installed so the fluid can be produced.The equipment installed as an artificial lift, that is maintained so that the well can produce optimally, will experience â€œwell problemsâ€ on the reservoir production, such as watercut, scaling, and other problems. If the k in a well has a high watercut but has heavy oil characteristics, it is necessary to increase oil production handled with ESP artificial lift in order to optimize the oil production. Keywords : electrical submersible pump, nodal analysis, artificial lift evaluation